Whole-stand growth and yield models for Pinus patula - Santiago-García, Wenceslao; De los Santos-Posadas, Héctor Manuel; Ángeles-Pérez, Gregorio; Valdez-Lazalde, José René; Corral-Rivas, José Javier; Rodríguez-Ortiz, Gerardo; Santiago-García, Elías (Instituto de Ecología, A.C., 2016)
Predicting the growth and yield of timber tree species is a prerequisite for planning sustainable forest management. The objective was to update several functions that integrate a compatible growth and yield system for Pinus patula, developed under the explicit whole-stand model approach. System parameters were estimated using seemingly unrelated regression. For that, forest biometric information was used from four periodical inventories conducted in 42 permanent plots of 400 m2 in Hidalgo, Mexico. Almost all the functions of the system had good fit and satisfactory graphical behavior in their original structure. A polymorphic growth pattern explains stand productivity, which is interrelated with growth equations of basal area, mean diameter and total stem volume per hectare. The mortality function corresponds to an exponential model fitted under non-linear least squares method. The re-fitted system broadened the range of the growth equations to 31 years. The new system suggests a maximizing volume rotation of about 20 years for the average site. These results suggest that the commonly used 40 year rotation period used in the management plans in the region could be shortened if a proper density management strategy is applied.